Effect of weed management practices on the performance of transplanted aman rice varieties - Ferdous, J; Islam, N; Salam, MA; Hossain, MS (Journal of the Bangladesh Agricultural University, 2016)
A field experiment was carried out to study the effect of weed management practices on the performance of transplanted aman rice varieties. The experimental treatments comprised three varieties viz. BR11, BRRI dhan39 and Binadhan7 and seven weeding treatments viz., weedy check, hand weeding at 15 and 35 DATs, application of early post-emergence herbicide Manage (Pyrazosulfuron ethyl), application of pre-emergence herbicide Rifit (Pretilachlor), Manage + one hand weeding at 35 DAT, application of Rifit + one hand weeding at 35 DAT and weed free. The experiment was laid out in a randomized complete block design with three replications. The results reveal that varieties should significant variation on plant height, number of total tillers hill-1, number of effective tillers hill-1, number of non-effective tillers hill-1, panicle length, number of grains panicle-1, number of sterile spikelets penicle-1, 1000-grain weight, grain yield, straw yield and harvest index. Grain yield was the highest in BRRI dhan39. Weeding regime had also significant effect on all the studied crop parameters except 1000-grain weight. The highest grain yield was obtained from weed free condition followed by hand weeding at 15 and 35 DATs. Interaction between variety and weeding regime had significant influence on all the studied crop parameters except 1000-grain weight. The highest grain yield was obtained from the interaction of BRRI dhan39 × weed free condition which was statistically identical (5.50 t ha-1) with interaction of variety BR11 × two hand weedings at 15 and 35 DATs. Therefore it may be concluded that BR11 rice could be cultivated using two hand weedings at 15 and 35 DATs for obtaining higher yield. J. Bangladesh Agril. Univ. 14(1): 17-22, June 2016